Serosurvey for Schmallenberg Virus in Alpine Wild Ungulates. Issue 1 (26th August 2013) - Chiari, M.; Sozzi, E.; Zanoni, M.; Alborali, L. G.; Lavazza, A.; Cordioli, P.
Summary Because Schmallenberg virus (SBV) was first reported in domestic ruminants in Northern Italy in February 2012, we conducted a serosurvey to assess the presence of SBV‐specific antibodies in free‐ranging alpine ruminants. The tested serum samples were from chamois (23) and red deer (352) hunted from 2007 to 2013. All of the serum samples collected through September, 2012, tested negative, whereas a single chamois serum and 21 red deer sera taken during the 2012–2013 hunting season tested positive for the presence of SBV antibodies. Because this serosurvey is suggestive of an active SBV circulation in Alpine wildlife, targeted surveillance should be performed on wild ruminants to monitor the spread of the virus and to assess the epidemiological role of wildlife at the interface with domestic animals.